DETERMINATION OF THE BEGINNING OF RAMADHAN AND SYAWAL IN INDONESIA (an Overview of Political and Historical Perspectives) - Azmi Muttaqin (UIN Walisongo Semarang, 2022)
This research departs from the existence of differences in theory and opinion in determining the beginning of the lunar month at the theoretical and practical level, there are two methods, namely Hisab and Rukyat. The existence of these differences is caused by three main things, namely first, in terms of legal determination, second, in terms of systems and methods of calculation. Departing from these different interpretations, various mass organizations (Society organizations) emerged in the matter of reckoning rukyat Indonesia such as NU (Nahdlatul Ulama), Muhammadiyah and others. The various differences are the responsibility of ulil amri which is none other than the Ministry of Religion of the Republic of Indonesia. Apparently the issue of determining the beginning of the lunar month is not only limited to the shariah level, but also the involvement of political elements in power at that time. Departing from that the researcher held a further overview of the ins and outs of the determination and its dynamics in each political era. This research is a qualitative research study of literature.